PEMBELAJARAN MATEMATIKA SD BERKARAKTER BERBASIS CAI-KONTEKSTUAL MENGGUNAKAN LAB VIRTUAL - Nanang Nanang (Program Studi Pendidikan Guru Sekolah Dasar STKIP Al Hikmah Surabaya, 2019)
Recently, various phenomena have emerged in the community that indicate conflicts in various circles in various aspects of life, giving the impression that the Indonesian nation is experiencing a crisis of ethics and self-identity. Character education is expected to be an alternative solution for behavioral and moral improvement. Meanwhile, from several reports, Indonesian students consider it difficult to do mathematical activities. One alternative to overcome these difficulties is through character learning based on Computer Assisted Instruction (CAI) -Contextual use of the Virtual Lab by conditioning students to learn by themselves according to their real life (daily life) rather than memorizing and students can develop their potential independently and creatively owned. For this reason, the writing of this paper is intended to develop and design a CAI-Contextual character based mathematics learning model using Virtual Lab as an alternative to improve the character quality and students' ability to do mathematics. Based on the results of theoretical studies and discussions, it was concluded that through the application of CAI-Contextual using a Virtual Lab in learning mathematics character in elementary school, it is expected to: (1) overcome the low ability of elementary students' mathematical thinking, (2) reduce the lack of effective learning models used by teachers in maximizing the potential that exists in elementary students, (3) increasing understanding of the facts learned, and (4) skillfully applying mathematics in solving problems of daily life, and (5) improving the quality of student character.